Alkimista, antropológus, archeológus - Pócsik, Andrea (Socio.hu Társadalomtudományi Szemle, 2013)
Nichols, Bill és Renov, Michael (2011) Cinema’s Alchemist. The Films of Péter Forgács (Visible Evidence 25). Minneapolis–London: University of Minnesota Press.